(untitled) (Bioscience Journal, 2015)
: The aim this work was to evaluate the genetic variability within and among populations grown on sisal region of Bahia. The genetic diversity of 140 population of sisal was analyzed using ISSR molecular markers. Samples were collected in six counties in Bahia. Eighteen primers of ISSR were used, in which nine of them were effective in the amplification of DNA samples to yield 143 polymorphic loci. The average percentage of polymorphism found in the population was 64%. The average heterozygosis (He) and Shannon-Wiener index (I) were 0.180 and 0.279, respectively. 73% of the molecular variance can be due to intrapopulation differences. The populations were divided into two groups according to their geographical location, showing a structure of genetic variability in space. The GST 0.235, enough to avoid that there is a strong population differentiation. The genetic structure of sisal can be exploited for the creation of gene banks for conservation in situ and ex situ to obtain individuals of good commercial quality. There is genetic variability among sisal genotypes. ISSR molecular markers are efficient to analyze the divergence between sisal genotypes, assisting improvement work.